Art and fashion: an experience at Recife’s art school (Revista de Ensino em Artes, Moda e Design, 2021)
Starting from the understanding of the Triangular Approach as a way to elaborate worldsbased on the interpretation of images and artistic objects, an art / educational activitydeveloped during the vacation course of the year 2020 will be presented, at theEscolinha de Arte do Recife (EAR), in order to record how the institution has beenoperating in the contemporary world. First, we will make a historical contextualization ofthe institution's emergence, from its pedagogical perspectives, and then reflect on theartistic activity of stamping with alternative materials, the contributions to the aestheticformation of children. Following artistic methods used by the artist Iza do Amparo, anartist presented during a vacation course module, the children, as will be seen, whencoming into contact with the artist's work and with the artist herself, were able to expandtheir aesthetic perceptions, and capacity for reflection on topics such as: Ethics,Environment and Local Culture.
Keywords: Art/education; Stamping; Iza do Amparo; Sustanaible